2018
DOI: 10.4103/jios.jios_123_17
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Rate of En masse Retraction and Anchorage Loss in Conventional Labial Appliance with Labial and Lingual Force: A Clinical Study

Abstract: The rate of en masse retraction and anchorage loss were compared between labial appliance with lingual force and conventional labial appliance. Subjects and Methods: The sample consists of 14 patients and they were divided into two groups. In Group 1 -labial appliance with lingual force, elastomeric chain was placed from the palatal surface of the canines to the palatal surface of the molars. In Group 2 -labial appliance with labial force, elastomeric chain was placed from the crimpable hook distal to lateral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…Sample size calculation was done using the comparison of rate of space closure between labial force method and T-loop spring method. As reported in previous publication 17,18 . The mean ± SD of rate of space closure in labial force method group was approximately 0.88 ± 0.05 mm, while in T-loop spring method group it was approximately 0.708 ± 0.157 mm.…”
Section: Sample Sizesupporting
confidence: 75%
“…Sample size calculation was done using the comparison of rate of space closure between labial force method and T-loop spring method. As reported in previous publication 17,18 . The mean ± SD of rate of space closure in labial force method group was approximately 0.88 ± 0.05 mm, while in T-loop spring method group it was approximately 0.708 ± 0.157 mm.…”
Section: Sample Sizesupporting
confidence: 75%
“…(17) In lingual orthodontics, the point of force application is on the lingual side and this difference in the aspect of point of force application and its varying distances from the center of resistance in both sagittal and vertical planes, are the key reasons why teeth respond differently to lingual technique (11,18) . Quraishi et al, (14) compared between labial appliance with lingual force and conventional labial appliance. The rate of retraction was faster and anchorage loss was lower with labial appliance with lingual force, thus indicating that this new technique In the present study, the canine retraction rate was measured clinically using dental vernier at monthly intervals.…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, torque is more difficult to control in lingual orthodontics (4,9,11,12) . This limitation of torque control during retraction in lingual orthodontics has been overcome by the use of labial appliance with lingual force instead of lingual appliance with lingual force (6,14) . Takemoto (6,8) compared the anchorage loss in bimaxillary protrusion subjects treated with labial and lingual appliances and concluded that a minimal amount of 0.1-0.5 mm of anchorage loss was observed with retraction of up to 7.9 mm with lingual appliances (6,8,13) .…”
Section: Introductionmentioning
confidence: 99%